An Econometric Analysis regarding the path of Non Performing Loans- A Panel Data analysis from Mauritian Banks and Implications for the Banking Industry - Polodoo, Viren; Seetanah, B.; Padachi, Kesseven; Sannassee, R.; Seetah, K. (Journal of Developing Areas, 2014)
The present study pertains to unravelling the internal (bank specific) and external (macroeconomic) determinants of nonperforming loans in Mauritius using annual report data from a panel of 10 existing banks and macroeconomic data for the period 2000 to 2012. The model used in the present instance comprises of a vector of bank specific and macro economic variables which include the inflation rate, lending interest rates, growth of the construction sector and tourism sector as well as global variables such as the Euro zones GDP growth. The model is tested both in a static and dynamic framework. Four estimation techniques are considered, viz Fixed Effects, differenced GMM, System GMM and Random coefficient estimation. The results indicate that, notwithstanding there are many significant factors influencing NPL, the most critical elements nevertheless remain declines in the construction sector and the rise in cross border loans. Interestingly, the study provides important policy insights which centres on the improvement of credit concentration guidelines as well as the modification of the MCIB reporting